Recent Developments in the Speciation and Determination of Mercury Using Various Analytical Techniques - Lakshmi Narayana Suvarapu; Sung-Ok Baek (Journal of Analytical Methods in Chemistry)
This paper reviews the speciation and determination of mercury by various analytical techniques such as atomic absorption spectrometry, voltammetry, inductively coupled plasma techniques, spectrophotometry, spectrofluorometry, high performance liquid chromatography, and gas chromatography. Approximately 126 research papers on the speciation and determination of mercury by various analytical techniques published in international journals since 2013 are reviewed.